2010
DOI: 10.1364/josaa.27.001529
|View full text |Cite
|
Sign up to set email alerts
|

Mueller matrix interpolation in polarization optics

Abstract: The question of the physical significance of the Mueller matrix average is addressed by means of an analysis of interpolation processes. We draw a comparison between two interpolation processes. The first one is related to the classical Euclidean metrics and the second one is based on the log-Euclidean metrics. Both the associated interpolation procedures are depicted with their underlying physical models. Addressing the question of the physical meaning of the log-Euclidean process of interpolation is founded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This is the way used by Arsigny [14] to define the LE distance on Symmetric Positive Definite matrices. Proving that this distance can easily be extended to HPD(4) matrices and is well adapted to coherency matrix interpolation was done in [11].…”
Section: Log-euclidean Distance On Coherency Matrix Spacementioning
confidence: 99%
See 2 more Smart Citations
“…This is the way used by Arsigny [14] to define the LE distance on Symmetric Positive Definite matrices. Proving that this distance can easily be extended to HPD(4) matrices and is well adapted to coherency matrix interpolation was done in [11].…”
Section: Log-euclidean Distance On Coherency Matrix Spacementioning
confidence: 99%
“…Following the definition of the LE distance, interpolating from H 1 =H(0) to H 2 =H(1) consists in changing the proportion of both the elements D 1 =log(H 1 ) and D 2 =log(H 2 ) constituting the thin laminae (see [11] for more details). This medium is thus characterized by an infinitesimal generator D = (1-t).D 1 + t.D 2 .…”
Section: Log-euclidean Distance On Coherency Matrix Spacementioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of the Mueller matrix introduces to each pixel in an image is named Mueller imaging [8,9]. ]Another representation of interaction of polarized light with media, named Jones matrix does not permit for changes such as degree of polarization, depolarization of beam incident on sample or emerging from it [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have demonstrated that the relevant information of turbid media can be derived by analyzing the backscattered polarization patterns of the sample [5][6][7][8][9][10][11][12][13][14] . All these studies are aiming at analyzing sample's properties using polarization patterns.…”
mentioning
confidence: 99%